2006
DOI: 10.1097/01.brs.0000199894.63450.70
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Screw Positioning in a New Anterior Spine Fixator on Implant Loosening in Osteoporotic Vertebrae

Abstract: Implant stability within each implant group was influenced by BMD and load bearing cross-sectional area. The angulation of the two screws did not have a significant influence on cut-out. As conclusion from this study, promising approaches for further implant development are: 1) increase of load-bearing cross-sectional area (e.g., larger outer diameter of the anchorage device), 2) screw positioning in areas of higher BMD (e.g., opposite cortex, proximity to pedicles or the endplates).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 64 publications
1
14
1
Order By: Relevance
“…This trend can be explained as a result of the superior biomechanical properties of angular stable plate or rod systems when compared with conventional implants [34,52]. In this context, the relevance of newly developed screw designs and their configuration within the VB have to be considered as well [33,72,75]. New expandable anterior devices can be implanted via thoracoscopic approaches; thus, reducing the perioperative morbidity and pain with better lung function as compared to conventional thoracotomies [8,15,50,65].…”
Section: Discussionmentioning
confidence: 99%
“…This trend can be explained as a result of the superior biomechanical properties of angular stable plate or rod systems when compared with conventional implants [34,52]. In this context, the relevance of newly developed screw designs and their configuration within the VB have to be considered as well [33,72,75]. New expandable anterior devices can be implanted via thoracoscopic approaches; thus, reducing the perioperative morbidity and pain with better lung function as compared to conventional thoracotomies [8,15,50,65].…”
Section: Discussionmentioning
confidence: 99%
“…Many biomechanical studies have demonstrated that pedicle screw fixation is highly correlated with BMD [27]. The screw-bone interface is a dynamic structure with differing mechanical characteristics in different portions of the implant surface.…”
Section: Discussionmentioning
confidence: 99%
“…Pedicle screw instrumentation is one of the most commonly used and rapidly growing forms of stabilization for spinal fusion. Transpedicular fixation, however, can be very challenging in the osteoporotic spine as mechanical stability of the pedicle screws is determined by bone mineral density (BMD) [9,27]. In addition, poor rigidity of the bone-screw contact can lead to loosening of the implant in osteoporotic patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be expected that triangulated double screw/double rod systems will achieve higher pullout strength than single rod/single screw systems, as several studies showed [30,37,[40][41][42]44]. A two-rod or twoscrew system however, has a high metal load for the patient and, especially in the surgery of spinal deformities in children with small and dyplastic vertrebrae, is more difficult and sometimes impossible to implant.…”
Section: Discussionmentioning
confidence: 99%
“…Like the Kaneda anterior spinal system [21], also the MACS TL twin screw device [37,41] and the MACS TL polyaxial screw XL device [42] have a two screw design with specific angles of the screws to each other in one vertebra. It is to be expected that triangulated double screw/double rod systems will achieve higher pullout strength than single rod/single screw systems, as several studies showed [30,37,[40][41][42]44].…”
Section: Discussionmentioning
confidence: 99%